2017
DOI: 10.1519/ssc.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Horizontally Loaded Movements to Sports Performance

Abstract: THE USE OF VERTICALLY LOADED EXERCISES, SUCH AS THE BACK SQUAT, DEADLIFT, AND OLYMPIC-STYLE LIFTS, ARE COMMONLY PRESCRIBED BY STRENGTH AND CONDITIONING PROFESSIONALS TO ENHANCE THE PHYSICAL QUALITIES OF ATHLETES. THESE METHODS HAVE BEEN SUPPORTED AS EFFECTIVE MEANS, MAINLY FOR NOVICE SUBJECTS, BUT THEIR EFFECTIVENESS AND TRANSFER HAS BEEN QUESTIONED IN MORE ADVANCED ATHLETES AND IN TRANSFER TO SPECIFIC PHYSICAL QUALITIES. THE EFFECTIVENESS OF VERTICALLY LOADED EXERCISE TO ENHANCE SPRINTING SPEED AND CHANGE OF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…In an attempt to explain some of the differences that have been found in studies like those of Loturco et al [ 8 ] and Contreras et al [ 7 ], it has been common to refer to the so-called “force-vector” theory [ 9 , 10 ]. According to this theory, sports skills can be classified on the basis of the direction of force expression relative to the global (world fixed) coordinate frame.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to explain some of the differences that have been found in studies like those of Loturco et al [ 8 ] and Contreras et al [ 7 ], it has been common to refer to the so-called “force-vector” theory [ 9 , 10 ]. According to this theory, sports skills can be classified on the basis of the direction of force expression relative to the global (world fixed) coordinate frame.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the deadlift, the load is applied perpendicular to the bodyand loadedin the horizontally plane, unlike the squat, which is a loaded in the vertical plane [3]. Horizontally loaded movements may be more beneficial for horizontally based sporting movements such as sprinting and long jump, which implies deadlifts may provide a greater transfer effect to these activities [3]. Taken as a whole, the results of this research suggests the biomechanical profile of the squat and deadlift.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast,thedeadlift, however, the deadlift starts in a mechanically difficultposition, requiring the lifter to generatethe entire force needed to move the bar off the floor, without the assistance of the stretch shortening cycle [2]. Finally, in the deadlift, the load is applied perpendicular to the bodyand loadedin the horizontally plane, unlike the squat, which is a loaded in the vertical plane [3]. Horizontally loaded movements may be more beneficial for horizontally based sporting movements such as sprinting and long jump, which implies deadlifts may provide a greater transfer effect to these activities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found wider bench press grips stimulate more of the lower (sternal) pec attachments. 57 For the clavicular portion pectoralis major, it appears narrower grips may be more effective. Research indicates anterior deltoid activity is most significant during incline (30 to 45 degrees) bench presses.…”
Section: Muscle Mechanics Chest and Triceps Muscles Activitymentioning
confidence: 99%